Contract of Sale According to Kosovo Legislation (Vallis Aurea, 2021)
The contract of sale represents one of the most important contracts on internal and external circulation of goods. This contract is considered one of the oldest and it has the same purpose in all the countries worldwide. With this contract, the seller is obliged to deliver the goods he sells to the buyer, in order for him to gain the right of ownership, whereas the buyer is obliged to pay the price as per the contract. validity conditions, resolution and consequences of resolution, etc.In some occasions, the contracts are subjects of different conflicts which reach the only solution through courts. Given the fact that there are different types of the contracts of sale, it is important that we make efforts in order to study them, difficulties we encounter with regards to the circulation of goods and money.